Effectiveness of Internal Focus Instructions for Improving Motor Performance in Continuous Training of Untrained Tasks - SASADA, Keita; KANAYAMA, Atsuki; TAKAHASHI, Hina; YAMAMOTO, Saki; MINAMI, Mayuka; TAKESADA, Yurika; IWATA, Akira; OMAE, Maki; MIKAMI, Hiroya; ARIHARA, Izumi; YABUTA, Hiromu (Rigaku ryoho kagaku, 2021)
[Purpose] External focus (EF) instructions have been shown to be more effective than internal focus (IF) instructions for improving motor performance. However, there is a possibility that the more effective type of instruction depends on the skill level and the intervention period. The purpose of this study was to examine which of IF and EF instructions was more effective for continuous training of untrained tasks. [Participants and Methods] Sixty-two university students were assigned to either the IF or EF groups. They trained for 14 consecutive days using IF or EF instructions for a pitching task with their non-dominant hand, and ball speed was measured. [Results] There was no significant interaction for changes in ball speed, but there was a significant main effect of time, and the ball speed of all participants increased significantly. [Conclusion] The results suggest that IF instruction is as effective as EF instruction in the continuous training of untrained tasks.